Navigating the Challenges of da'wah: Insights from Buya Hamka's Tafsir Al-Azhar - Affandi, Yuyun; Faiq Azmi , Muhammad; Sutiawan, Iwan; Muzajjad , Ahmad (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
The challenges of da'wah in the contemporary era have significant complexity. The diversity that occurs in society requires inclusive preaching to be a challenge in itself. with technological developments and ethical moral problems today's. demands that da'wah to be carried out adaptively but still maintain the basic principles of Islamic values. In this context, in-depth research regarding the theme of the challenges of da'wah needs to be carried out. one of them is through reading Hamka's interpretation of Al-Azhar. This interpretation is important because it provides a holistic and contextual view of Islamic teachings. Hamka's straightforward interpretation character, with the character of adaby ijtima'i and a deep touch of Sufism, allows the values in it to be used to face the challenges of da'wah with a solid scientific and spiritual foundation. The research method used is a thematic interpretation study with a focus on the themes of da'wah which have been grouped by Hamka. This research reveals that Hamka's thoughts in the interpretation of Al-Azhar are still very relevant as a provision and ideological basis as well as a practical reference in facing the challenges of da'wah that occur today. regarding technological challenges, no specific discussion was found, However, principle values were found that can still be contextualized according to current challenging conditions.